Developing poster based on diversity of Nepenthes in Padat Karya Forest Krayan, North Kalimantan - Ilma, Silfia; Zulfadli, Zulfadli; Superli, Superli; Rupa, Darius (University of Muhammadiyah Malang, 2018)
Nepenthes is a unique carnivores plant that can be found in Padat Karya forest, Krayan at the North Kalimantan. The existence of these plants can be used as a media of learning so that learning activities become more contextual. The aims of this study are 1) to know the diversity of Nepenthes in Padat Karya forest, 2) to determine the feasibility of learning media in the form of poster developed from the results of the Nepenthes diversity research. This research consisted of two stages. The first was research stage which involved inventory, identification, and diversity index determination of Nepenthes. The second stage was development research i.e developing the results gained from the first stage into poster form. The research and development model employed in this study was the modified-Borg and Gall (2006) model. There were five steps conducted, namely (1) need analysis, (2) planning, (3) develop the preliminary form of product, (4) preliminary field testing, and (5) main product revision. The results showed that the diversity index value of Nepenthes was categorized as âmediumâ. In addition, based on the validation and response obtained, the poster developed was feasible to be utilized as a learning media in senior high school.